2019
DOI: 10.3389/fmicb.2019.02181
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Endophyte Bacterial Community Structure Across Two Panicum Grass Species

Abstract: Panicum represents a large genus of many North American prairie grass species. These include switchgrass (Panicum virgatum), a biofuel crop candidate with wide geographic range, as well as Panicum hallii, a close relative to switchgrass, which serves as a model system for the study of Panicum genetics due to its diploid genome and short growth cycles. For the advancement of switchgrass as a biofuel crop, it is essential to understand host microbiome interactions, which can be impacted by plant genetics and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
(68 reference statements)
3
11
0
Order By: Relevance
“…Leymus chinensis is an ecologically and economically important herbage that is widely distributed in the grasslands of Inner Mongolia and is a native perennial rhizome grass with prominent forage value and great palatability (Zhang et al , 2018). However, knowledge regarding the root microorganisms associated with L. chinensis remains limited, although root‐associated microbiomes have been extensively studied in other related plants (Yamamoto et al , 2018; Poudel et al , 2019; Singer et al , 2019). In addition, the microbial community structure of root‐associated microbiomes is different between bacterial and fungal communities, and this difference depends on the chemical and physical properties of the soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leymus chinensis is an ecologically and economically important herbage that is widely distributed in the grasslands of Inner Mongolia and is a native perennial rhizome grass with prominent forage value and great palatability (Zhang et al , 2018). However, knowledge regarding the root microorganisms associated with L. chinensis remains limited, although root‐associated microbiomes have been extensively studied in other related plants (Yamamoto et al , 2018; Poudel et al , 2019; Singer et al , 2019). In addition, the microbial community structure of root‐associated microbiomes is different between bacterial and fungal communities, and this difference depends on the chemical and physical properties of the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The OTUs, richness and diversity of bacterial and fungal communities in the rhizosphere from L. chinensis were higher than those observed in the root endosphere (Table S1). Root‐associated microbiomes have to overcome the immune defence mechanisms of plants to inhabit the endosphere compartment, which generally leads to reduced density and diversity in the microbial communities compared with that observed in rhizosphere soil communities (Singer et al , 2019). Previous reports have also shown that microbial richness and diversity gradually increase from the root endosphere to the rhizosphere soil and that microbial density is generally lower in the root endosphere than in the rhizosphere (Hacquard et al , 2015; Edwards et al , 2015; Yamamoto et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Singer et al (2019) observed a large core endophytic switchgrass microbiome dominated by root-colonizing bacterial genera such as Streptomyces , Pseudomonas , and Bradyrhizobium , while rhizosphere diversity was more variable between their two sampling sites. Likewise, Singer et al (2019b) observed different core bacterial classes associated with upland and lowland switchgrass ecotypes, with each ecotype preferentially enriched for Alphaproteobacteria and Actinobacteria, respectively. For our study, out of 268 families, only two associated with the majority (>=90%) of our rhizosphere samples (Xanthobacteraceae and Sphingomonadaceae) and less than half (n = 110) associated with more than 10% of our samples.…”
Section: Discussionmentioning
confidence: 93%
“…Culture-independent techniques, PCR-denaturing gradient gel electrophoresis (DGGE) and Illumina MiSeq sequencing of the 16S rDNA of root endophytic bacterial communities confirmed the selectivity of genotypes in durum wheat, as different cultivars hosted significantly different bacterial communities in their root tissues (Agnolucci et al 2019b). However, Singer et al (2019) found conserved community structures across different genotypes of Panicum virgatum and Panicum hallii.…”
Section: Recruitment Of Bacterial Root Endophytes By Host Plantsmentioning
confidence: 91%